2022
DOI: 10.1001/jamapediatrics.2022.0152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Freshly Irradiated vs Irradiated and Stored Red Blood Cell Transfusion on Cerebral Oxygenation in Preterm Infants

Abstract: IMPORTANCE Gamma irradiation of leukoreduced red blood cells (RBCs) prevents transfusion-associated graft-vs-host disease but also exacerbates storage lesion formation in RBCs. It is unknown whether freshly irradiated RBCs are more efficacious than irradiated and stored RBCs in preterm infants with high transfusion requirements.OBJECTIVE To examine whether transfusion of freshly irradiated vs irradiated and stored RBC components improves cerebral oxygen delivery in preterm infants with anemia. DESIGN, SETTING,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…A randomized trial in New Zealand of 42 preterm infants showed a small improvement in cerebral oxygenation by near‐infrared spectroscopy in infants receiving freshly irradiated RBCs versus irradiated and stored RBCs 67 . Although statistically significant, it is not clear whether the small differences are clinically significant and whether larger trials are needed.…”
Section: Pediatricsmentioning
confidence: 99%
“…A randomized trial in New Zealand of 42 preterm infants showed a small improvement in cerebral oxygenation by near‐infrared spectroscopy in infants receiving freshly irradiated RBCs versus irradiated and stored RBCs 67 . Although statistically significant, it is not clear whether the small differences are clinically significant and whether larger trials are needed.…”
Section: Pediatricsmentioning
confidence: 99%
“…We excluded ineligible studies according to the exclusion criteria as follows: (1) ineligible study designs such as case series, narrative review, animal study, meta-analysis;…”
Section: Selection Criteriamentioning
confidence: 99%
“…Preterm infants are at high risk for anemia due to immaturity, impaired erythropoiesis, and frequent blood sampling [ 1 , 2 ]. Therefore, preterm infants have one of the highest transfusion requirements within the hospital setting [ 3 ], especially very (VLBW) or extremely low birth weight (ELBW) infants [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physiological rationale that red blood cell (RBC) transfusion improved oxygen carrying capacity was a tantalizing prospect. In this issue of JAMA Pediatrics, Saito-Benz et al 1 renew such hopes in a novel proof-of-concept randomized clinical trial (RCT) of irradiating RBCs on the day of transfusion (which the authors termed fresh irradiation) to boost cerebral oxygen saturation. Their PICOT (population/ patient, intervention, comparison, outcome, and time) question was whether stable very low-birth-weight preterm infants requiring a top-up transfusion who received freshly irradiated RBCs showed an improvement in the noninvasively measured brain oxygenation compared to those who received routinely irradiated RBCs in a neonatal intensive care unit with high transfusion thresholds.…”
mentioning
confidence: 99%
“…However, results of the ARIPI trial suggested that age is not important. 7 In assessing the potential benefits of freshly irradiated RBC for preterm transfusion, it is important to consider whether the surrogate primary outcome in the RCT by Saito-Benz et al 1 is robust. Does the short-term physiological surrogate outcome of crSO 2 (or related indexes) embody long-term outcomes?…”
mentioning
confidence: 99%